Radiological risk assessment and environmental analysis - Till, John E.; Grogan, Helen A. (Oxford : Oxford University Press, 2008)
This volume explains methods used for estimating risk to people exposed to radioactive materials released to the environment by nuclear facilities or in an emergency such as a nuclear terrorist event.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Radiation dosimetry; Radiation -- Safety measures; Health risk assessment